Analisis Penentuan Harga Pokok Produksi Dengan Metode Full Costing, Variable Costing dan Activity Based Costing Pada Pabrik Air Minum Syifa’ P2S2 Sukorejo Situbondo - Himawan Pradipta; Su'ud Wahedi; Endi Sihabuddin (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2023)
The selling price is a crucial aspect of a product. Considering the selling price is one of the factors that will influence consumer decisions in buying a product. So that the determination of the selling price of the product must be done carefully and with integrated considerations. Through production costs, operational costs, desired profit targets, people's purchasing power, competitors' selling prices, general economic conditions, product price elasticity, and so on. The selling price policy is influenced by the cost of production and affects the success or failure of the company in achieving its goals. Thus, the As-Syifa' Bottled Drinking Water Factory (AMDK), as one of the producers of drinking water circulating in the midst of the Sukorejo Islamic Boarding School environment, must carefully consider the method of determining the cost of production that is applied. Departing from this thought, the researcher intends to conduct research at As-Syifa's AMDK by applying the full costing method, variable costing, and activity based costing. This research was conducted at Jln. KHR. Syamsul Arifin, Sukorejo village, Banyuputih, Situbondo. Precisely in one of the Islamic boarding school business units that produces drinking water. Data sources consist of primary and secondary sources. Data obtained through observation, interviews with managers, and documentation. From the results of the discussion, the following conclusions are obtained: (1) the As-Syifa' AMDK factory has so far used the conventional method in determining its HPP and obtained a HPP of Rp. 9,612.- (2) from the results of applying the full costing method, variable costing, and activity based costing obtained by different HPP which can be taken into consideration by As-Syifa's AMDK manager.